Design and Position Analysis of Health Office Chair for Sedentary Crowd - Mo Lingling; Shi Zhixin; Luo Yufeng; Xie Dongfu; Li Chengwu; Zou Jianxing (Jixie chuandong)
Based on the principle and method of ergonomics， the structure and motion characteristics of the lumbar joint of human body are analyzed. According to the above features and combined a discontinuously movable mechanism in the limb， an office chair for health is a hybrid mechanism that has 3R motion with bifurcated motion and can realize the human body waist joint movement is proposed. Then the operation mode is analyzed. The results show that， the hybrid mechanism has instantaneously three degrees of freedom at the constraint singular configuration. At this time， the method of redundant drive can be used to change the three-rotation mode into the two-rotation mode. Finally， the forward solution analysis equations of the hybrid mechanism in different operation modes are derived. The results show that the mechanism is completely decoupled.